Neue Ausgabe sämtlicher Werke - Liszt, Franz 1811-1886; Liszt, Franz 1811-1886 (Editio Musica, 2014)
Of the early versions of works included in Supplementary Volume 10, particular interest is expected in the first versions of the notably popular Consolations cycle and the monumental Grand solo de concert of 1850. In the first version of Consolations the third movement was a style hongrois piece whose thematic material Liszt used again later in the first piece of the Hungarian Rhapsodies published in 1851. The first version of the Grand solo de concert shows that the original concept did not include the slow "movement" that would be placed in the middle of the work and recapitulated towards the end in the final version - a characteristically Lisztian feature that would reappear a few years later in the Sonata in B flat minor. A detailed preface in English and German, including new research results, numerous manuscript facsimiles and critical notes make this volume of the New Liszt Edition a specially important publication of scholarly value. Simultaneously with the cloth-bound Complete Edition volume, its paperback for practical purposes is also published, the contents of which, except for the critical notes, is identical with the Complete Edition volume.